EPISTIMOLOGI KRITISISME IMMANUEL KANT - Syaiful Dinata (Sekolah Tinggi Agama Islam Sadra, 2021)
This research is motivated by Immanuel Kant's tho This research is motivated by Immanuel Kant's thoughts regarding his efforts to reconcile the prolonged conflict of rationalism and empiricism groups, which in the future Kant's thinking became the forerunner of the initial foothold of the thinkers after him. The research method that the author uses is qualitative with a library research approach. The data collection technique in this study is a documentation technique, namely by collecting important data files that support research. The result of this research is that Immanuel Kant's criticism, philosophy of criticism is a combination of rationalism and empiricism. This school of criticism is also known as Kant's criticism, because Kant was the first to criticize and analyze the two sources of knowledge and combine them. During his 80 years (w. 1804) of life, Kant produced many works, including: (1) his 1781 essay on a critique of pure reason. (2) 1788 his essay on the critique of the ratio of practice. (3) 1790 his essay on the critique of the ratio of judgment/judgment, and Immanuel Kant's Epistemology of criticism, Immanuel Kant's thoughts in the field of epistemology are fully devoted in his work entitled “Critique of Pure Reason”. Kant's thoughts inspired many philosophers after him to present the idea of ​​human knowledge. ughts regarding his efforts to reconcile the prolonged conflict of rationalism and empiricism groups, which in the future Kant's thinking became the forerunner of the initial foothold of the thinkers after him. The research method that the author uses is qualitative with a library research approach. The data collection technique in this study is a documentation technique, namely by collecting important data files that support research, both primary sources such as the book Characters of Philosophers and the Golden Era of Philosophy by Nurnaningsih Nawawi as well as other secondary sources that support the topic of discussion. The result of this research is that Immanuel Kant's criticism, philosophy of criticism is a combination of rationalism and empiricism. This school of criticism is also known as Kant's criticism, because Kant was the first to criticize and analyze the two sources of knowledge and combine them. Then, Immanuel Kant, Flashes of Life and his major works, Immanuel Kant was born in Konigsberg, East Prussia (now Germany), on April 22, 1724. Born as the fourth of six children of his father, of Scottish descent. Her mother is of German descent. Kant's parents were saddle-makers and staunch followers of the Pietism movement. During his 80 (1804 w) years of life, Kant produced many works, including: (1) his 1781 essay on a critique of pure reason. (2) 1788 his essay on the critique of the ratio of practice. (3) 1790 his essay on the criticism of the ratio of judgment/judgment, and Immanuel Kant's Epistemology of criticism, Immanuel Kant's thoughts in the field of epistemology are fully devoted in his work entitled Critique of Pure Reason. Kant's thoughts inspired many philosophers after him to present the idea of ​​human knowledge.